Agricultural Communications Practitioners’ Perspectives on Skills and Competencies Graduates Need to Be Career Ready: A Mixed Methods Study with Implications for Undergraduate Programs - Elizabeth Wyss; Adam Cletzer (Journal of Applied Communications, 2023)
Agricultural communications (ACOM) programs contend with continuous disruptive change caused by changing audiences, media technologies, and communications objectives. To keep curricula current, ACOM programs often turn to ACOM practitioners for guidance on how to prepare graduates. This explanatory sequential mixed methods study investigated ACOM practitioners in Missouri's perspectives on which skills and competencies were important for career readiness, as well as why they were important and under what circumstances. “Writing” and “reporting” skill categories were deemed most important. The qualitative follow-up strand revealed several clarifying themes. First, foundational skills, such as writing and reporting, are important because they are often the skillsets that are perennially relevant in a fast-changing field. Second, instruction in even basic technical communication skills prepares graduates to keep up with changing digital design technology on their own while in the workforce. Third, political savviness is a necessary skill for navigating differences both within the agricultural industry and with consumers. Finally, broad agricultural industry knowledge is more important in graduates than narrow technical expertise. This study has implications for ACOM faculty responsible for the continued revision of ACOM curricula.
Keywords: Skills; competencies; program development; curriculum